Influence of parallel and series U-loop configurations on the thermal behaviour of energy piles - Faizal, Mohammed; Bouazza, Abdelmalek (Symposium on Energy Geotechnics 2023, 2023)
Energy piles are foundation piles that have heat exchanger pipes installed in them for exchanging geothermal energy between buildings and the ground through the use of a ground source heat pump (GSHP). This is a cost-effective and environmentally friendly method to supplement heating and cooling of buildings. Heat transfer occurs between the piles and the ground through a heat transfer fluid circulating in the pipes. The heat exchanger pipes in the piles are commonly made from polyethylene pipes formed into U-loops [e.g., 1, 2, 3, 4, 5, 6, 7]. The U-loops are configured into series or parallel configurations to circulate water in the pipes. A number of studies have investigated the thermal and thermo-mechanical behaviour of energy piles with U-loop heat exchangers [e.g., 1, 2, 3, 4, 5, 6, 7]. Despite this widespread research, the fluid flow and temperature variations in the individual U-loops are not well understood for parallel and series U-loops in the piles. Given that the fluid flow behaviour varies between the two configurations [8], it can be hypothesised that the thermal behaviour of the energy piles may vary as well. This study investigates the influence of series and parallel U-loop configurations on the variations in fluid temperatures and flowrates in the individual U-loops of energy piles, and the effects of these variations on the geothermal energy extracted by the piles. Heating experiments were conducted on a set of four field-scale energy piles installed below a 5-storey building in Brighton group sandy soils. The energy piles have a length of 15 m and diameter of 0.9 m, but different numbers of U-loops (1, 2, 3, and 4 U-loops in Piles 1, 2, 3, and 4, respectively). The fluid temperatures and flowrates were monitored in the individual U-loops of the piles that were connected to a plumbing manifold located in the monitoring room (Figure 1). A comparative thermal performance analysis of the two configurations was conducted to derive conclusions on the preferred configuration for improved thermal performance of the piles. The flowrate variations and change in fluid temperatures in the individual U-loops at Day 15 of group tests are shown in Figure 2. The flowrates were inconsistent between the U-loops in the parallel configuration but remained constant in the series U-loops. Heat exchange occurred in all the U-loops in parallel, whereas only the first few U-loops in the series configuration exchanged heat with the ground. The results suggest that all the energy piles in the group with parallel U-loops were thermally active and could improve the performance of energy pile systems compared to energy piles with U-loops in series.